АПРОКСИМАЦІЯ ОБВІДНИХ КВАЗІСИНУСОЇДАЛЬНИХ ЦИФРО-АНАЛОГОВИХ СИГНАЛІВ - Карасінський, О.Л.; Тесик, Ю.Ф.; Мороз, Р.М. (Інститут електродинаміки НАН України, Київ, 2022)
The principle of setting the instantaneous values of signals with smoothed envelopes using first-order basis splines, which is optimal from the point of view of equipment costs and the computing power of a microprocessor is proposed. A computer model of a multiphase generator has been developed with the help of which the principles of stepwise and linear approximation of the signal envelope have been investigated. References 11, figures 5, table 1.